O-025 Geographical influence on aneurysm treatment outcomes and retreatment rates. (4th July 2012) - Prestigiacomo, C; Mocco, J; Hetts, S; Nesbit, G; Murayama, Y; Macdougall, C; Johnston, S; Ge, G; Jung, S; Gholkar, A; Lopes, D; Perl, J; et al.
Abstract : Background and Purpose: Recent data from HELPS, Cerecyte and MAPS trials demonstrate that aneurysms can be safely and effectively treated using various coils. Comparing outcomes between trials can be difficult due to different trial designs. The very low bleeding or rebleeding rates of treated aneurysms has led most investigators to use angiographic outcomes to compare devices. Angiographic assessments are operator-dependent, potentially affecting trial results. We sought to understand the impact of geography on aneurysm retreatment in patients enrolled in the Matrix and Platinum Science (MAPS) Trial. Materials and Methods: Post hoc analysis was performed on MAPS trial data. Patients were stratified into two groups based on treating center location. Centers were categorized as being in North America (NA) or International (INTL). Baseline patient demographics, comorbidities, and aneurysms characteristics that could impact treatment outcomes were analyzed. Procedural complications and clinical and angiographic outcomes were compared. Results: 407 patients (115 ruptured, 292 elective) from 28 NA sites and 219 patients (113 ruptured, 140 elective) from 15 INTL sites were evaluated. Patient demographics differed between NA and INTL, with the most significant (p<0.0001) differences being the proportion of female patients (76% vs 60%), ruptured aneurysms (28% vs 52%), Caucasians (86% vs 72%) and two or more Cardiovascular Risk Factors (31% vs 15%). A H&H score of III or IV was more prevalent in the NA ruptured patients (33% vs 21% p=0.0452). NA treated more posterior circulation aneurysms (16% vs 8% p=0.0064), more aneurysms with neck ≥4 mm (39% vs 31%, p=0.0353) and more patients >55 years old (54% vs 40%, p=0.0014). The angiographic core lab found 56.2% of NA aneurysms were completely or nearly completely occluded post-procedure vs 73.5% in INTL (p=0.0002). Packing density of >25% was similar in NA (41.3%) and INTL (37.4%) groups. Stents were used more frequently in unruptured aneurysms treated in NA than INTL (44% vs 19%, respectively, p<0.0001). At 30 days, NA ruptured patients were more likely to have been discharged than INTL patients (85.2% vs 66.4%, p=0.0101). At 1 year, there was no difference in the proportion of patients alive and free of disability (>90% of ruptured and >96% of unruptured), and no difference in the proportion of residual aneurysms (36.6% vs 28.7%, p=0.082). Ruptured aneurysms were more likely to have been retreated in NA vs INTL (21.7% vs 4.4%, p=0.0001); there was no significant difference in retreatment rates among unruptured aneurysms. NA sites retreated 49.2% of aneurysms that were operator-assessed as having residuals at 1 year, while INTL sites retreated 19.0% (p=0.0156). This difference in retreatment resolved at 2 years, with residual aneurysm retreatment rates being nearly equivalent on preliminary 2-year follow-up data. Conclusion: Endovascular treatment practices for intracranial aneurysms are very different between NA and INTL sites, likely reflecting practice variation rather than individual patient differences. Retreatment of partially occluded aneurysms tends to occur more frequently in the first year in NA but later elsewhere. This trend has critical value when interpreting trials results that report short-term outcomes. Competing interests: C Prestigiacomo: Thermopeutix, Edge Therapeutics, Stryker. J Mocco: None. S Hetts: None. G Nesbit: None. Y Murayama: None. C Macdougall: None. S Johnston: None. G Ge: Stryker Neurovascular. S Jung: Stryker Neurovascular. A Gholkar: None. D Lopes: None. J Perl: None. D Tampieri: None. A Turk: None.